As dinâmicas de circulação do acontecimento fechamento do Queermuseu na mídia gaúcha - Garcez, Cadiani Lanes (2020)
This study aims to describe the dynamics of media circulation around the closing event of the Queermuseum in the newsmedia in Rio Grande do Sul. Queermuseu - Cartography of differences in Brazilian art was an art exhibition that took place at Santander Cultural, in Porto Alegre, from August 16 to September 10, 2017. The methodology used is the case study (BECKER, 1997, BRAGA, 2008 and YIN, 2001) combined with the analysis of circulation (CARLÓN, 2017). The main concepts employed were mediatization and circulation (BRAGA 2012 and 2017, FAUSTO NETO, 2006, 2008, 2009, 2010 and 2015, FERREIRA, 2017, VERÓN, 1997, 2004, 2007 and 2014) and happening (FRANÇA, 2012 and QUÉRÉ, 2005 and 2012). By problematizing the context of the society in mediatization, it was possible to map the circulation process and identify some social actors involved: individual actors, media and institutions (Verón, 1997). The unexpected character in the closing of the Queermuseu makes it a happening, according to Quéré (2005), and to understand its dimension, it is necessary to think of it as a result of a serial chain of other occurrences. For the analysis, publications were collected in the regional media of Rio Grande do Sul - represented in this work by Correio do Povo, GaúchaZH, G1-RS, Jornal do Comércio and Sul 21, dating from before the exhibition was opened to the public, to right after a recommendation for its reopening (from August 11 to September 29) made by the Federal Public Ministry (MPF). Carlón (2017) presents an analysis of circulation divided into phases, highlighting how they happen from a case. The phases are marked by movements of the circulation, which can be vertical ascending, starting in digital social networks and then ascending to traditional media; descending verticals, when they go from traditional media to digital social networks; or horizontal, circulating in only one of the media systems. Based on the author's proposal, the analysis was divided into four phases: opening of the exhibition, closing of the exhibition, interstice and MPF recommendation. Vertical (descending and ascending) and horizontal movements were noticed, with the descending movement standing out in the first phase; in the second phase, ascending movements; while in the third and fourth phases there were horizontal movements. In this way, some circulation dynamics of the closing event of the Queermuseu were studied, identifying communication flows produced by different social actors, involved in the complex context of a society in mediatization.